2008
DOI: 10.4269/ajtmh.2008.78.750
|View full text |Cite
|
Sign up to set email alerts
|

Human IgG Antibody Response to Glossina Saliva: An Epidemiologic Marker of Exposure to Glossina Bites

Abstract: Abstract. The evaluation of human antibody response specific to arthropod saliva may be a useful marker of exposure to vector-borne disease. Such an immunologic tool, applied to the evaluation of the exposure to Glossina bites, could be integrated in the control of human African trypanosomiasis (HAT). The antibody (IgG) response specific to uninfected Glossina fuscipes fuscipes saliva was evaluated according to the vector exposure and trypanic status in individuals residing in an HAT-endemic area. A high level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…More generally, a correlation between the level of specific IgG anti-saliva antibodies and the risk of disease has been demonstrated for different vector-host models. [30][31][32] We also found that the enhanced risk of developing ZCL was associated with the production of anti-saliva antibodies of IgE isotype. One may suggest that individuals who have allergies are more prone to develop a Th2 immune response and therefore have an increased risk of developing leishmaniasis.…”
Section: 27mentioning
confidence: 63%
“…More generally, a correlation between the level of specific IgG anti-saliva antibodies and the risk of disease has been demonstrated for different vector-host models. [30][31][32] We also found that the enhanced risk of developing ZCL was associated with the production of anti-saliva antibodies of IgE isotype. One may suggest that individuals who have allergies are more prone to develop a Th2 immune response and therefore have an increased risk of developing leishmaniasis.…”
Section: 27mentioning
confidence: 63%
“…aegypti saliva because previous studies have demonstrated that the IgG response is a useful biomarker for exposure to mosquito bites. 16,33,34 Further investigations are therefore needed to establish whether the antibody response to saliva is age dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Poinsignon and others have shown that antibody responses to Glossina saliva could be a useful indicator of exposure with high diagnostic value. 16 Antibody responses to saliva can also provide a measure of exposure to mosquitoes, such as Culex. 17,18 Recently, it has been demonstrated that the IgG response to whole saliva from Anopheles gambiae is a reliable biomarker of exposure and the risk for developing malaria infection/morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, salivary proteins may also be immunogenic and induce in vertebrates an antisaliva antibody (Ab) response that may be taken as a measure of exposure to vector bites. This strategy has been investigated for several vectors of human pathogens such as ticks [10], triatomine bugs [11e13], sand flies [14,15], tsetse flies [16,17] and mosquitoes [18e22]. More specifically, as far as malaria is concerned, it should be pointed out that IgG Ab response to Anopheles saliva or salivary gland extracts has been shown to represent an effective biomarker of human exposure to bites of malaria vectors [23e26].…”
Section: Introductionmentioning
confidence: 99%